(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nguyen TTB, Nhai NT, Xuan LT, Duc HV, Duy ND, Hanh TTH, Nhien NT. 2025. Assessing the nucleotide sequence diversity of COI, COII, CYTB, ND5 in several silkworm strains raised in Vietnam. Biodiversitas 26: 1061-1068. The selection of silkworm breeds is currently a subject of great interest in Vietnam, where assessing genetic diversity plays a crucial role. The main objective of this study was to evaluate the genetic diversity characteristics of the COI, COII, Cytb, and ND5 loci of mtDNA in 15 parental Bombyx mori (Linnaeus, 1758) lines raised in Vietnam. This includes 10 high-yielding white cocoon strains (bivoltine) and 5 low-yielding yellow cocoon strains (multivoltine), which are well adapted to the local climate conditions in Vietnam. The research used the PCR technique with specific primer pairs, performed sequencing using the Sanger method, and processed the data with BioEdit, DnaSP, and MEGA 11 software. The nucleotide sequencing results revealed a high A+T content in all four loci, particularly at the ND5 locus, where the total A+T content reached 84.94%. The study indicated that COI, COII, and ND5 markers alone are insufficient for differentiating between strains. However, the nucleotide sequences of the COII and ND5 loci can be used to identify the 5 multivoltine yellow cocoon native strains of Vietnam. Additionally, the nucleotide sequence of the Cytb locus can be used to distinguish these 5 native silkworm strains. These results will support breeders in identifying and differentiating native Vietnamese silkworm breeds.